Sustainable development of companies using the ERP system as a fundamental tool of digital transformation - Jan Špatenka; Miloš Koch (Trends Economics and Management, 2021)
Purpose of the article: The purpose is to verify that ERP system implementations are in accordance with the company growth. There is no doubt that the ERP system as a representative of digitalisation tools aims at optimisation of resources and processes, while also contributing to sustainability. Methodology/Methods: The article is based on processing and sorting of secondary data published by the Czech Statistical Office. All relevant data were issued in different formats and structures so they needed to be parsed, cleaned and unified. It would not be possible to achieve expected results without such data transformation requiring knowledge in the field. To ensure higher validity of the study, the dependence between two researched aspects was observed in the lowest possible detail of the data and then summarised into present the final result. Scientific aim: The aim is to identify the relationship between the ERP system implementations and company growth. The study assumes that companies are motivated to digital transformation if it helps them to increase their production or do not temporarily slow it down because of the lifecycle and consequences of the implementation covering investment, deployment and usage of the ERP. Findings: Although the number of Czech companies using an ERP system is not constantly growing, the enterprise production is increasing during the reference period. This phenomenon is noticeable in almost every NACE industry in years 2015, 2017 and 2019. Even though the number of firms using the ERP is not clearly growing, as there is a fall in 2017, the general trend between 2015 and 2019 is increasing. Conclusions: As there is no negative effect of implementation of the ERP system on company growth, enterprises are willing to invest into their digital transformation and thus to support sustainable development as a whole.
Keywords: M15; M21; 650; ERP system; company growth; sustainable development; digital transformation